Pengembangan Game Terapi Bagi Anak Autisme Berbasis Motion Capture dengan Metode Optimasi Kalman Filter - Antoni DM, Nikolas; Rudi Susanto; Ridwan Dwi Irawan (Fakultas Teknik Universitas Hamzanwadi, 2024)
Children with autism spectrum disorder often face challenges in developing motor skills and social interaction abilities. This research aimed to develop an interactive motion capture-based therapy game that could assist autistic children in practicing their motor skills through an enjoyable play experience. The Kalman Filter optimization method was employed to enhance the accuracy and quality of motion detection in the motion capture process. The development of this therapy game involved consultations with therapists, psychologists, and relevant experts in designing game activities tailored to the needs of autistic children. Motion capture technology was utilized to capture the children's body movements in real-time, while the Kalman Filter algorithm was implemented to filter and optimize the acquired motion data. The game interface was designed to be simple, featuring attractive visual objects, bright colors, and familiar sounds. The testing results demonstrated that the application of the Kalman Filter method could increase motion detection accuracy up to 90%, ensuring a more responsive and immersive play experience for the children. This therapy game proved effective in improving motor skills, body coordination, as well as motivation and engagement of autistic children in the therapy process. This research contributes to the development of an enjoyable and effective interactive therapy solution to assist autistic children in developing essential skills for daily life